Formal methods: foundations and applications : 18th Brazilian Symposium, SBMF 2015, Belo Horizonte, Brazil, September 21-22, 2015, Proceedings /: 18th Brazilian Symposium, SBMF 2015, Belo Horizonte, Brazil, September 21-22, 2015, Proceedings. (2016) - Unknown
No abstract available